A socio-legal study on citizenship of undocumented foundling children in West Malaysia / Farhana Sofea Norjahan … [et al.] - Norjahan, Farhana Sofea; Azmadi, Noor Amiera Syamimi; Hassan, Nor Maisarah; Zainal Azman, Nur Azrina (2013)
This study is aimed to reflect the importance of recognizing the rights of undocumented foundling children located in West Malaysia. The research will be based on qualitative type of research by focusing on data gathered from various written sources as well as interviews conducted with legal experts. It will focus on the consequence of such absence on the rights of the said children in the Act. The research concludes that the Act has not recognized this type of children and thus, some recommendations have been proposed at the end of this research in view of improving the Act and thereby increase the protection of such children who are facing with citizenship difficulties.